DIVERTÍCULO DE KOMMERELL: A PROPÓSITO DE UN CASO (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2025)
Kommerell diverticulum is a rare congenital anomaly of the aortic arch. It is characterized by the presence of one or several diverticula in the thoracic aorta, usually ascending and arch, from which aberrant arteries such as the subclavian arteries or aortic arches can emerge. It presents asymptomatically with an incidental imaging finding or in patients with symptoms such as dysphagia, cough or chest pain. Treatment is surgical in most cases, although a few patients benefit from endovascular procedures. The clinical case of an asymptomatic 45-year-old female patient is presented, who presents with refractory hypertension that is difficult to control, with a pressure difference between upper and lower limbs, in which a tomographic discovery of several Kommerell diverticula is made (in number). of 5) in ascending aorta and arch without vascular aberration, added to aortic coarctation, which is unusual. Due to the unusual imaging finding at the presentation of this rare congenital anomaly, the clinical case is presented.